Teaching arts and science with the new social media - Wankel, Charles (Cutting-edge technologies in higher education, 2011)
This book will cover a wide range of approaches to applying social media in teaching arts and science courses. The first part of the book, SOCIAL LEARNING AND NETWORKING APPROACHES TO TEACHING ARTS & SCIENCE, will cover collaborative social media in writing courses, the use of wikis as a platform for co-creation of digital content, and powerful data sharing. Part two, SOCIAL MEDIA PEDAGOGIES FOR THE FUTURE OF ARTS & SCIENCE LEARNING, explores the expansive vistas enabled by these new technologies. The use of content posting in public social media forums as an enabler of critical reflection is considered, as will the use of social media to augment face-to-face meetings. The third part, LEARNING ARTS & SCIENCE IN THREE-DIMENSIONAL VIRTUAL WORLDS, will look to the opportunities and downsides of this immersive technology. Design recommendations for instructors will be put forth. Part four, BLOGGING AND MICROBLOGGING IN A NEW EPOCH OF TEACHING ARTS & SCIENCE, will look at a welter of applications and implications for teaching practices. For example, the use of Twitter as a sandbox where students share ideas before arriving in class or as back-channels to classes is explored.